2016
DOI: 10.12788/jcso.0409
|View full text |Cite
|
Sign up to set email alerts
|

The impact of inpatient rehabilitation on outcomes for patients with cancer

Abstract: The impact of inpatient rehabilitation on outcomes for patients with cancer T he American Cancer Society reports that 1.6 million people are diagnosed with cancer each year, of whom 78% are aged 55 years or older. The 5-year survival rate for cancer is 68%. 1 Almost 15.5 million living Americans have been diagnosed with cancer. 2 Many patients with cancer have difficulty walking and with activities of daily living. Patients with primary brain tumors or tumors metastatic to the brain may present with focal weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…[7] There is a ceiling effect on improvement in FIM. [8] When patients reach an adequate level of function, they are discharged to home. Therefore, properly selected patients at a lower level of function may make more improvement than patients admitted with a higher FIM score.…”
Section: Discussionmentioning
confidence: 99%
“…[7] There is a ceiling effect on improvement in FIM. [8] When patients reach an adequate level of function, they are discharged to home. Therefore, properly selected patients at a lower level of function may make more improvement than patients admitted with a higher FIM score.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study results, previous studies showed that approximately 18% of cancer patients with low functional capacity return to an acute setting. 3,4,19 They also found that FIM scores were associated with the return rate to an acute setting. However, the other factors associated with the return of cancer patients to acute care settings are still unclear.…”
Section: Hospital Length Of Stay (Los)mentioning
confidence: 93%
“…The existing literature also showed that improvements in FIM scores resulted in decreased strain on resources and burden of caregivers. 3,4 Common barriers to cancer rehabilitation were lack of physician/oncologist knowledge about rehabilitation benefits, lack of rehabilitation facilities, and lack of cooperation between interdisciplinary team members, and these factors negatively affect the functional recovery of cancer survivors. 17 Apart from the above-mentioned factors, the clinical profile of cancer patients admitted to rehabilitation facilities may also affect the overall prognosis and duration of hospital stay.…”
Section: Hospital Length Of Stay (Los)mentioning
confidence: 99%
See 2 more Smart Citations